Sistem Informasi Pemesanan Dan Pembayaran Sewa Mobil Pada Puskopka Jateng Berbasis Web - Ikhmar Panji Nugraha; Y Yusup; Ana Wahyuni (STIKOM Tunas Bangsa Pematangsiantar, 2025)
Managing services in the transportation sector such as vehicle rentals requires a structured and efficient system. Currently, the car rental booking and payment process at PUSKOPKA JATENG is still via WhatsApp or Instagram Direct Message, making it difficult to manage data and communicate with renters. The purpose of this research is to focus on designing a web-based car rental booking and payment information system at PUSKOPKA JATENG using the Waterfall model. This system is designed to provide convenience to renters in the process of booking and paying for car rentals online, as well as providing convenience to admins in managing data such as renter data, cars, rental packages, bookings, payments and transaction reports. The interface design was designed using Figma, while for system development using HTML, Laravel and MySQL as the database. To ensure all features run properly, testing is required, in this case the researcher used the Black Box method as a method in system testing.